Survey effective factors on childbirth with an interval of less or more than two years among women referred tohealth clinics of Zahedan in 1997-1998 - M. Modarres; Sh Ghasizadeh; A . Mehran; T . Dadghah (Tehran University of Medical Sciences, 2001)
This was an analytical study that was conducted to determine effective factors on childbirth with an interval of less or more than two years in health clinics of Zahedan in 1997-1998."nThe samples consisted of 400 women with a childbirth interval of less than two years and 800 women with a childbirth interval of more than two years."nThe women with the following criteria were surveyed: gestational age at the time of delivery (27 months or more ), no abortion during the interval of two last childbirth and living with their husbands during the investigation period. Moreover, women's demographic data (such as age, education), the quality of their last pregnancies, the role of men in contraception and the contraceptive methods were also analyzed."nThe results indicated that there was a significant relationship between the follwing variables and establishing an interval of childbirth: maternal delivery age, education, number of male children and the number of the last pregnancy with an interval of childbirth (pRegarding the unwanted pregnancies, the findings revealed that lactation 15.83% and lactation pills 53% were caused childbirth with an interval of less than two years, while, IUD 76.47% caused childbirth with an interval of more than two years and contraceptive injections 46.43% caused an interval of 2-3 years."nThere was a significant statistically relationship between contraceptive method and childbirth interval (p <0.001 )."nThe participation of couples in establishing childbirth interval and applying IUD were confident methods in performing a childbirth interval of more than three years."nIt is recommended that women should be trained enough for the role of lactation as a contraceptive method. They also required training to apply other contraceptive methods coincidental.